'A female voice is instrumental': gender, propaganda, and coerced labor on the Eastern Front, 1943-1945 - Barton, Deborah (Labor History, 2022)
This article examines the role of local, female propagandists utilized by the German army on the Eastern Front during WWII. Although the work they undertook aligned with postwar notions of collaboration, the propagandists’ experiences at the hands of the Wehrmacht, in a context of a violent war and repressive occupation, constitutes coerced labour in multiple forms. Regardless of the women’s motivations for working for the Wehrmacht, they entered a relationship of domination and dependence with the occupation force. While female propagandists numbered far fewer than their male counterparts, they held a particular importance for German high command who believed that their “feminine” traits, such as empathy and charm, helped the Wehrmacht influence and control the largely female civilian population. At the same time, their work on the frontlines encouraging Red Army soldiers to defect crossed traditional gender boundaries. In this task too, the women were valued for their gender with German authorities believing that Soviet soldiers, largely deprived of female contact, would be particularly receptive to the charm of a woman’s voice. Such coerced labor on behalf of the Wehrmacht rendered these women vulnerable not only to German violence, but also to Soviet accusations of collaboration and its associated reprisals.
Number: 3 _eprint: https://doi.org/10.1080/0023656X.2022.2146077
Keywords: Eastern front; Propaganda; Wehrmacht; coerced labor; gender; war